A global systematic review of the influence of competition on the outcomes of fauna conservation - Aurelie M. Kanishka; Nick Dexter; Chris R. Dickman; Natasha M. Robinson; David B. Lindenmayer (Conservation Science and Practice)
Abstract Ecosystems typically exhibit resilience to disturbances, yet excessive pressure can disrupt species interactions, resulting in biodiversity loss. Conservation interventions strive to safeguard ecosystems and reinstate vital ecological functions. Competition between animals plays a pivotal role in ecosystem persistence and dynamics, but its significance is often underestimated in conservation research. We conducted a global review that analyzed 147 articles, focusing on the impact of competitive interactions between animals on conservation interventions. We found a tendency for researchers to retrospectively interpret observed patterns of interactions as competitive. Negative outcomes, such as species declines, were frequently associated with competitive interactions. Despite efforts to predict outcomes using characteristics of the competition process, we found no consistent patterns of outcomes based on these characteristics. Our findings underscore the considerable influence that competition may have on conservation outcomes, emphasizing a need for proactive consideration of competition dynamics as part of planning conservation interventions. By integrating animal competition into conservation planning, monitoring, and mitigation efforts, unexpected negative impacts can be minimized, fostering more effective conservation outcomes.